Longitudinal development of visual working memory precision in childhood and early adolescence - Burnett Heyes, S; Zokaei, N; Husain, M (Elsevier, 2016)
© 2016. Visual working memory (VWM) is the ability to hold in mind visual information for brief periods of time. The current study investigated VWM precision development longitudinally. Participants (N = 40, aged 7-11 years) completed delayed reproduction sequential VWM tasks at baseline and two years later. Results show age-related improvement in recall precision on both 1-item and 3-item VWM tasks, suggesting development during childhood and early adolescence in the resolution with which both single and multiple items are stored in VWM. Probabilistic modelling of response distribution data suggests age-related improvement in precision is attributable to a specific decrease in the variability (noisiness) of stored feature representations. This highlights a novel developmental mechanism which may underlie longitudinal improvement in VWM performance, crucially without invoking improvement in the number of items that can be stored. VWM precision provides a sensitive metric with which to track developmental changes longitudinally, shedding light on underlying cognitive mechanisms.